(untitled) (Mongolian Journal of Arts and Culture, 2025)
This article provides a historical overview of the development and transformation of Mongolia’s academic degree and title system based on archival materials, government decrees, and scholarly sources. During 1921–1945, academic training was primarily conducted abroad, especially in the Soviet Union. Between 1940 and 1990, domestic universities and research institutions established academic councils, adopting a two-tiered system of “Candidate of Science–Doctor of Science” and the academic titles “Associate Professor–Professor,” under centralized supervision by the Higher Attestation Commission. Since the 1990s, Mongolia has transitioned to an internationally recognized framework comprising Master, Doctor (Ph.D) and Doctor of Science (Sc.D) degrees, integrating credit-based doctoral programs and decentralized defense councils within universities. The field of culture and art studies marked a milestone in 1978 with the first domestic dissertation defense, laying the foundation for independent scholarly development. This study highlights the evolution of institutional policies, the legal framework, and the continuing need for quality assurance and international alignment in Mongolia’s academic degree system. Монгол Улсад эрдмийн зэрэг, цол хамгаалах, олгох тогтолцоо үүсэн хөгжсөн түүхэн тойм Хураангуй: Энэхүү өгүүлэл нь Монгол Улсад эрдмийн зэрэг, цол хамгаалах, олгох тогтолцооны үүсэл, өөрчлөлт, эрх зүйн болон институцийн зохион байгуулалтын хөгжлийг архивын баримт, тогтоол, тушаал, хэвлэгдсэн бүтээлүүдэд тулгуурлан тоймлов. Эрдмийн зэрэгтэй хүмүүсийг 1921-1945 онд гадаадад (голлон ЗХУ) бэлтгэж, хамгаалуулах үйл ажиллагаа давамгайлж байсан бол, 1940-1990 онд дотоодын их, дээд сургууль болон шинжлэх ухааны байгууллагуудын дэргэд зөвлөлүүд байгуулагдан “дэд эрдэмтэн-доктор” гэсэн эрдмийн зэрэг, “доцент-профессор” цол олгох төвлөрсөн баталгаажуулалт (Дээд комисс)-тай тогтолцоо төлөвшсөн. 1990 оноос олон улсын жишигт нийцүүлэн магистр, доктор (Ph.D) ба шинжлэх ухааны доктор (Sc.D) зэрэг бүхий кредитэд суурилсан сургалт, хамгаалуулах зөвлөлөөр баталгаажуулах хэлбэрт шилжив. Соёл, урлаг судлалын чиглэлд 1978 оноос дотоодын хамгаалалтууд эхэлсэн нь салбарын хөгжлийн чухал үе шат байв. Тойм нь өнөөгийн байдал, цаашдын бодлого тодорхойлоход судлаачдад суурь лавлах болно. Түлхүүр үгс: аспирантур, хамгаалуулах зөвлөл, Ph.D, Sc.D, дээд боловсролын бодлого, дүрэм, журам